We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
96
1
avatar

Q1)

thankies

 Mar 13, 2019
edited by Guest  Mar 13, 2019
 #1
avatar+7531 
+1

\(\quad (f-g)(x)\\= f(x) - g(x)\\= (3x^5+6x^2-5) - (2x^4+7x^2-x+16) \\ =3x^5+6x^2-5-2x^4-7x^2+x-16\\ =3x^5-2x^4-x^2+x-21\)

.
 Mar 13, 2019

4 Online Users

avatar